8.° Congreso Internacional de la Química de los Cementos (8.° CIQC) Comité Científico para Europa, Asia y África (CEAA). Reunión del 22-VI-83 en París - Calleja, José (Materiales de Construcción, 1983)
This information paper deals with the subject treated in the mentioned meeting, the third of those celebrated by the Committee. This meeting was not previously programmed and had a character merely informative. Many questions related to the Scientific Program were treated in the meeting and a final proposal was prepared by the Committee to be sent to the President of the Latin-American Committee and Coordinator of the three Scientific Committees, Prof F. de A. Basilio.